2016
DOI: 10.1104/pp.16.00460
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Sensing via the Ethylene Response Transcription Factor RAP2.12 Affects Plant Metabolism and Performance under Both Normoxia and Hypoxia

Abstract: Subgroup-VII-ethylene-response-factor (ERF-VII) transcription factors are involved in the regulation of hypoxic gene expression and regulated by proteasome-mediated proteolysis via the oxygen-dependent branch of the N-end-rule pathway. While research into ERF-VII mainly focused on their role to regulate anoxic gene expression, little is known on the impact of this oxygen-sensing system in regulating plant metabolism and growth. By comparing Arabidopsis (Arabidopsis thaliana) plants overexpressing N-end-rule-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 43 publications
2
67
0
Order By: Relevance
“…Suc exerts a very positive effect on Arabidopsis survival (Banti et al, 2008). Experiments using the 35S:D-RAP2.12 line demonstrated that constitutive expression of D-RAP2.12 results in stronger fermentative metabolism leading to lower carbohydrate availability and decreased tolerance to hypoxia (Paul et al, 2016). Tolerance was restored by feeding exogenous Suc, indicating that low levels of carbon reserves were the most likely reason for reduced anoxic resistance in 35S:D13RAP2.12 plants (Paul et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Suc exerts a very positive effect on Arabidopsis survival (Banti et al, 2008). Experiments using the 35S:D-RAP2.12 line demonstrated that constitutive expression of D-RAP2.12 results in stronger fermentative metabolism leading to lower carbohydrate availability and decreased tolerance to hypoxia (Paul et al, 2016). Tolerance was restored by feeding exogenous Suc, indicating that low levels of carbon reserves were the most likely reason for reduced anoxic resistance in 35S:D13RAP2.12 plants (Paul et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The lower expression of DIN6, coding for an Asn synthase, observed in D-RAP2.12 and 35S: MA-RAP2.3 plants (Fig. 6) may reflect the altered amino acid metabolism in plants expressing a stable version of ERF-VII proteins (Paul et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It controls mitochondrial respiration and TCA cycle enzymes, offering a genetic handle to adjust mitochondrial function when oxygen becomes limiting (Paul et al, 2016). RAP2.12 undergoes proteasome-mediated proteolysis through the N-end rule pathway under normoxic conditions and is protected from degradation under hypoxia (Gibbs et al, 2011;Licausi et al, 2011).…”
Section: Nitric Oxidementioning
confidence: 99%
“…Fermentation is an alternative pathway for the production of pyruvate under hypoxia, normally produced in the Krebs cycle, when oxygen is available. However, fermentation has disadvantages in relation to the aerobic pathway, such as lower ATP production, accumulation of toxic metabolites, and reduction in cytosolic pH (Paul et al, 2016). The accumulation of metabolites, like lactate, alcohol, alanine, succinate, and even malate, are markers of active metabolic pathways (van Dongen and Licausi, 2015;Paul et al, 2016).…”
Section: Introductionmentioning
confidence: 99%